Valorisation of glycerol by-product of biodiesel production from crude palm oil (CPO) by catalytic conversion - Shofiyah Nada; Hendro Juwono; Chonlada Ritvirulh (My University, 2024)
Valorisation of glycerol through catalytic conversion conducted using KOH base catalysts with a mass ratio of KOH/glycerol of 0.08 (w/w) was carried out at temperature variations of 230 °C and 300 °C with feedstock variations of pure glycerol (98%) and crude glycerol with a total reaction time of 2 hours. Crude glycerol was obtained from the by-product of biodiesel transesterification from crude palm oil (CPO) using a KOH catalyst of 1% by weight of crude palm oil with variations in CPO:methanol such as 1:3, 1:6, and 2:1, which were performed at 60 °C for 4 hours at stirring speeds of 400 rpm. The largest percentage of crude glycerol conversion was obtained from the variation CPO: methanol (2:1) of 30.67%. The GC-MS characterization of glycerol catalytic conversion products revealed that the highest yield percentage is on the variation of pure glycerol feedstock at 230 °C, with the long-chain hydrocarbon fraction in the form of stearic acid compounds having the highest abundance percentage (abundance percentage of 26.54%). Catalyticconversion of pure glycerol feedstock variations at a reaction temperature of 300 °C resulted in formic acid (abundance percentage of 24.68%) with the greatest abundance and oxalic acid (abundance percentage of 2.28%). Meanwhile, the feedstock variation of crude glycerol produced 2-propenoic acid (abundance percentage of 5.04%) and acetone (abundance percentage of 2.84%), as well as hexadecanoic acid with the largest abundance percentage (32.04%). These findings demonstrated that catalytic glycerol conversion with KOH catalysts produced compounds with a wide range of industrial applications.
Keywords: Valorisation; Catalysis for Biomass Conversion